Central mucoepidermoid carcinoma in mandible: Case report of a clear cell variant with immunohistochemistry analysis - Massillamani Francis; Beshia Arnold; Santana B Natarajan; Deivanayagi Muthusamy (Journal of Indian Academy of Oral Medicine and Radiology, 2023)
Mucoepidermoid carcinoma (MEC) is the most common malignancy of the salivary glands that are extremely infrequent in the jaws and is termed central or Intraosseous mucoepidermoid carcinoma. Central mucoepidermoid carcinoma (CMEC) is known to affect the middle age group and has a slight female predilection. Most of these carcinomas mimic benign odontogenic lesions and very few present as locally aggressive lesions accompanied by clinical signs such as pain, swelling, movement of teeth, and loss of sensation of the inferior alveolar nerve. We are presenting a rare case of central mucoepidermoid carcinoma in a 66-year-old male patient with uniqueness in its arrival at diagnosis. This case substantiates the importance of collaborated histopathological and radiological investigations in the precise diagnosis of such locally aggressive carcinoma with metastatic potential while emphasizing the subsequent surgical reconstruction and its excellent prognosis.